Antenna diversity reception with correlated Rayleigh fading signals - Fang, Li Quan (2008)
Antenna diversity reception is one of the most powerful techniques to combat multipath fading in wireless communication systems. The three commonly used linear diversity combining techniques are maximal ratio combining(MRC), equal gain combining(EGC) and selection combining(SC). Generally, statistical independence in the fading of each diversity branch is assumed for simplicity. This assumption is valid if only the diversity antennas are sufficiently separated, generally larger than a half wavelength. As the size of receiver (the hand phone, for example) tends to be smaller, the space available for diversity antennas mounted on the receiver is limited so that the channel fading becomes correlated. In this thesis, two analysis methods are proposed to conduct the performance analysis of diversity reception with correlated Rayleigh fading signals.